Estudio del impacto de la marca turística Vilcabamba en base a un análisis de percepción - Maldonado Ortiz, Adriana Mile (2022)
Vilcabamba Tourist Brand was chosen as the object of study, as it is known as the Island of Longevity, because in this place we can find people who are over 100 years old and for this reason it has become very distinguished for tourism. The general goal of the research is to study the impact of the Vilcabamba tourist brand based on a perception analysis, for its fulfillment three specific objectives are proposed, the first objective: to define the variables to be measured according to the elements that compose the Vilcabamba tourist brand, analyze the level of perception generated by the Vilcabamba tourist brand in relation to the flow of tourism to the parish, analyze the impact that the Vilcabamba Tourist brand has generated in the offer of tourist services. For the elaboration of the first objective, a bibliographical research of the Vilcabamba tourist brand was carried out, to know what the logo, isotype, imago-type, chromatic scale and through a matrix it was verified with the elements that the tourist brand has, carrying out a conceptualization and description based on the elements of the design and finally the variables were defined to be able to formulate the questions that were applied in the survey of objective two. In the second objective, a questionnaire of 15 questions was elaborated with a sample of 374 national tourists; the questions were formulated according to the variables established in objective one. After tabulating and obtaining the results of the interview, through an impact measurement matrix, an assessment scale was established to measure the level of perception created by the tourist brand and its positioning in the mind of the tourist who visits Vilcabamba, where the results were in a range of 0.30/1, low scale, which means that the current tourist brand did not have a major impact on visitors. For the third objective, a matrix of inspection and participation of actors by activity was prepared, in order to establish the bidders to be interviewed. After the results were obtained from the interviews, an interpretation was made to find out if these people were aware of the existence of the tourist brand and what the concept of it expresses, and if the elements that make it up state the identity of the Vilcabamba parish. It was also evident that the current tourist brand is not contributing to the development of the place and much less has influenced the tourist's travel decision or is helping to increase sales in their businesses. Based on this, a matrix was developed to measure the impact of the tourist brand, generating a criterion in the bidders whose weight reaches 0.37/1, with a low scale, which means that the current tourist brand is not benefiting at all in the dynamization of the economy of the tourist businesses of the Vilcabamba parish. It is concluded that the current tourist brand does not have a great impact, according to the perception of tourists and providers of tourist services, which is why it does not represent a factor of influence in the final decision of the tourist to visit the Vilcabamba parish. It is concluded that the current tourist brand does not have a great impact, according to the perception of tourists and providers of tourist services, which is why it does not represent a factor of influence in the final decision of the tourist to visit the Vilcabamba parish. The creation of a new tourism brand is recommended where local actors are participants in the project that will benefit everyone in that area.